Increase in Blood–Brain Barrier Permeability is Modulated by Tissue Kallikrein via Activation of Bradykinin B1 and B2 Receptor-Mediated Signaling - Zhang Q; Tan J; Wan L; Chen C; Wu B; Ke X; Wu R; Ran X (Dove Medical Press, 2021)
Qin Zhang,1 Juan Tan,1 Li Wan,1 Chao Chen,1 Bin Wu,2 Xijian Ke,1 Rongxue Wu,3 Xiao Ran4 1Department of Anesthesiology, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, Hubei, People's Republic of China; 2Laboratory of Platelet and Endothelium Biology, Department of Transfusion Medicine, Wuhan Hospital of Traditional Chinese and Western Medicine (Wuhan No.1 Hospital), Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, Hubei, People's Republic of China; 3Department of Biological Sciences Division/ Cardiology, University of Chicago, Chicago, IL, 60637, USA; 4Department of Emergency, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, Hubei, People's Republic of ChinaCorrespondence: Xiao Ran Email ranxiao1001@tjh.tjmu.edu.cnAim: Disruption of the blood-brain barrier (BBB) is a critical pathological feature after stroke. Although tissue kallikrein (TK) has used in the treatment of stroke in China, the role of TK in modulating BBB permeability is not clear.Methods: We investigated the effect of different doses of TK on BBB by in vivo assessments of Evans blue (EB) and sodium-fluorescein isothiocyanate (FITC) leakage and in vitro assessments of the integrity of BBB and monolayers of microvascular endothelial cells (BMVECs). The expression of zonula occludens-1 (ZO-1) and bradykinin receptor-mediated signaling in BMVECs was detected.Results: A significant increase in BBB permeability was observed in the mice treated with high dose of TK. However, standard and medium doses of TK could only enable sodium-FITC to enter the brain. The result of in vitro study indicated that high-doses of TK, but not standard and medium-dose of TK, reduced normal BBB integrity accompanied by a decreased expression of zonula occludens-1 (ZO-1), upregulated the mRNA levels of bradykinin 2 receptor (B2R) and endothelial nitric oxide synthase (eNOS) and the abundance of B2R. Moreover, standard-dose of TK exacerbated lipopolysaccharide-induced BBB hyperpermeability, upregulated the mRNA levels of bradykinin 1 receptor (B1R) and inducible nitric oxide synthase (iNOS), increased the abundance of B1R and reduced the abundance of ZO-1; these effects were inhibited by TK inhibitor.Conclusion: TK can disrupt tight junctions and increase normal BBB permeability via B2R-dependent eNOS signaling pathway, aggravate impairment of BBB via B1R-dependent iNOS signaling pathway, and consequently serve as a useful adjunctive treatment for enhancing the efficacy of other neurotherapeutics.Keywords: tissue kallikrein, blood-brain barrier, bradykinin, permeability